Tumbling controls bean weevils - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Simply turning bags of beans upside down twice a day is the easiest way to stop the larvae of the common bean weevil causing damage. With regular disturbance the larvae soon die of exhaustion. The larvae of the common bean weevil (Acanthoscelides...